Provisional Agenda for the Thirty-First Meeting of the IMFC. (Policy Papers; Policy Paper ;, 2015)
The following is the provisional agenda for the Thirty-First Meeting of the International Monetary and Financial Committee, which is to be convened at the IMF's Headquarters in Washington, D.C. on April 17, 2015.